Carvings on the parapet wall - sequences from Mahabharata- Khandava forest burning; Below the parapet wall Beautifully carved miniature temple towers - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ] The iconography of the carved reliefs is unknown. We can recognise Lord Brahma seated on a swan fighting an elephant which could be Indra's mount Airavatha. (2) There is a burning forest and this is the episode where the Khandava forest is burnt by Arjuna and Krishna in order to help Agni.